AN EXPLORATORY STUDY ON THE IMPACT OF ORGANIZATIONAL SILENCE IN HIERARCHICAL ORGANIZATIONS: TURKISH NATIONAL POLICE CASE - Karaca, Hasan (European Scientific Journal, ESJ, 2013)
As being the main ingredient of organizations, employees possess information, experience, institutional knowledge, and ideas about their organizations. They also encounter many problems at the all stages of their work. Although it is expected from them to report the problems or share the solutions and information they have, they sometimes choose to remain silent. Understanding the employees’ perspectives are very important for better understanding the reasons they behave in an undesired manner. This study is aimed at determining what reasons that negatively affect employees’ decisions speak up and the extent they feel the given reasons lead them to remain silent. The research showed that administrative and organizational reasons are the most effective reasons impacting employee silence. Reassuring trust from executives by ensuring spaces for employees’ vocal participation and rebuilding the communication bridges between managers and subordinates will help increase the performance and efficiency of the organization as a result.